Repression and autogenous stimulation in vitro by bacteriophage lambda repressor. - Dottin, R P (1975)
Purified lambda repressor protein is shown to reduce the lambda DNA-directed synthesis of proteins in vitro as determined both by net amino-acid incorporation and by analysis of specific lambda-coded proteins resolved by sodium dodecyl sulfate/polyacrylamide slab gel electrophoresis. By means of different lambda DNA templates carrying deletion and point mutations in the operators o-L or o-R, it has been possible to demonstrate repression of the synthesis of two classes of lambda proteins. The synthesis of one, class c, appears to be controlled from the operator o-L and is more efficiently repressed at low concentrations of the repressor than that of the other class of repressible lambda proteins, class d, which is controlled from the operator o-R. Several other proteins synthesized in vitro are not repressible. Some of these are coded by the J-att region. In addition, the repressor appears to have another activity, that of stimulating the synthesis of a protein identified as the repressor itself. Lambda repressor appears to stimulate its own synthesis by acting at prm, a site defined by the cis-acting mutation prm 116.